(untitled) (CIPEEX, 2026)
Introduction: Autism Spectrum Disorder (ASD), classified by the DSM-5 as a neurodevelopmental disorder, is characterized by restricted patterns and difficulties in communication and social interaction, with emotional, cognitive, motor, and sensory manifestations beginning in childhood. Although motor development is not a diagnostic criterion, studies indicate that motor deficits are frequently present and impact cognitive, linguistic, and social aspects, making early recognition of these characteristics essential for effective intervention. Objectives: To determine whether the motor deficits presented by children with autism spectrum disorder can impact other areas of development. Methodology: This is a systematic literature review with a qualitative approach, based on the interpretation of scientific studies addressing motor development in children with ASD. Results: The results showed that approximately 88.6% of the participants were male. Motor delays were observed in up to 90% of cases, with impairment in fine (38.5%) and gross (6.7%) motor skills. Furthermore, 83.7% presented cognitive impairment and 81.8% presented below-average mental performance. Regarding motor function, the averages were 81.73% for posture and 75.91% for locomotion. Dyspraxia was identified in 100% of cases evaluated through hippotherapy. The data demonstrate a correlation between initial motor deficits and impairments in language, communication, and functional autonomy. Conclusion: Children with ASD present motor and cognitive delays that affect their development. Early intervention is essential to minimize these impacts. Further research should include larger sample sizes and ongoing monitoring.